Closed-loop graphite recycling from spent lithium-ion batteries through bioleaching - Roy, Joseph Jegan (2023)
Research into the recycling of electrode materials has gained attention due to the exponential increase in spent and discarded lithium-ion batteries (LIBs). While cathode electrode recovery has perennially been a research priority due to its economic benefits, anode electrode (graphite) recycling has yet to be accomplished. Currently, the focus has shifted to recycling the anodes from spent LIBs to deal with the scarcity of graphite resources and protect the environment because the anode is a crucial part of a LIB. The primary goal of this research is to recycle and regenerate anode graphite from the bioleaching residue. Unlike other hydrometallurgical LIB recycling, the bioleaching residue contains a considerable amount of iron salts with unleached cathode metal. Graphite was recycled using mild acid cleaning to remove vast amounts of iron salts and unleached cathode materials, followed by calcination treatments. Inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis revealed that the regenerated graphite had a purity of 99.78%. The morphology and structure of the regenerated graphite were confirmed to be identical to the commercial material using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy. The regenerated graphite samples show excellent electrochemical performance, with a charging/discharging capacity higher than 400 mAh/g and a retention rate of 100% after 200 cycles, surpassing commercial graphite (366 mAh/g).